DAMPAK PANDEMI COVID-19 TERHADAP USAHATANI KRISAN POTONG DI KECAMATAN SAMIGALUH KULON PROGO, YOGYAKARTA - mare, Monica Lasmaria simare; Budiraharjo , Kustopo; Setiadi, Agus (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
This study was conducted with the aim of analyzing the comparison of the amount of production, costs, revenue, income and R/C Ratio of the cut chrysanthemum farmers in Samigaluh before and during the Covid-19. The research method is a case study method with a sampling technique by census with the total sample of farmes is 30 before the Covid-19 and during Covid-19 only 12 farmers were trying to plant crysanthemums. Data analysis methode that used is descriptive and quantitative methods. Data comparison analysis was carried out using paired sample t test. The results of the study show that the cost before the Covid -19 was Rp. 8.843.295 while at the time of the Covid-19 was Rp.5.092.551. This shows a decrease in costs during the Covid-19 by 42,41%. The average production before the Covid-19 was 10.533 stalks while at the time of the Covid-19, it was 7.190 stalks. This shows that there is a decrease in average production during the Covid-19 by 31,74%. The average income of farmers before the Covid-19 was Rp. 15.120.000 while at the time of the Covid-19 it was Rp. 1.220.333. This shows a decrease in farmer income by 91,93%. The R/C ratio before the Covid-19 was 1,73 while at the time of the Covid-19 it was -0,77. This indicates a decrease in the R/C ratio by 144,5%. The income received by farmers before the Covid-19 was Rp. 6.376.706 while during the Covid-19 it was -Rp. 4.166.033. This indicates a decrease the level of income by 166%.